2021
DOI: 10.3390/diagnostics11060935
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of CD40/CD40L Inflammatory Pathway Molecules in Carotid Plaques from Moderate-and-Severe Obstructive Sleep Apnea Patients

Abstract: A chronic inflammatory process characteristic of obstructive sleep apnea promotes vascular endothelial dysfunction and atherogenesis. This process can lead to destabilization and rupture of cardiovascular plaques, which clinically manifests as an acute coronary syndrome or stroke. The aim of this study was to investigate the inflammatory pathway leading to plaque destabilization in non-to-mild and moderate-to-severe groups of OSA patients. This prospective study involved enrollment of patients scheduled for en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In this study, we assessed the importance of 24 features to OSAHS, and we were surprised to nd that LDL-C, Cr, carotid plaque, A1c and BMI made major contributions to OSAHS. Studies have shown an increased prevalence of OSAHS in patients with metabolomics, chronic kidney disease, carotid plaques, diabetes and obesity (25)(26)(27)(28)(29), which is consistent with our ndings. Importantly, we evaluated the ability of ML models created by ve algorithms to distinguish between OSAHS and non-OSAHS diseases, namely the commonly used Random Forest, boosting, SVM, and logistic regression and MLP methods.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we assessed the importance of 24 features to OSAHS, and we were surprised to nd that LDL-C, Cr, carotid plaque, A1c and BMI made major contributions to OSAHS. Studies have shown an increased prevalence of OSAHS in patients with metabolomics, chronic kidney disease, carotid plaques, diabetes and obesity (25)(26)(27)(28)(29), which is consistent with our ndings. Importantly, we evaluated the ability of ML models created by ve algorithms to distinguish between OSAHS and non-OSAHS diseases, namely the commonly used Random Forest, boosting, SVM, and logistic regression and MLP methods.…”
Section: Discussionsupporting
confidence: 93%
“…The severity of OSA was significantly associated only with MCP-1. The CD40 was nearly significant ( p <0.056), suggesting that the CD40/CD40L inflammatory pathway together with MCP-1 may contribute to plaque instability and rupture in OSA ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of inflammatory pathway, CD40-CD40L, enhances leukocyte recruitment to the sites of vascular inflammation and stimulates macrophages to produce matrix metalloproteinase (MMP). This process is associated with atherosclerotic plaque formation ( Li et al, 2020 ; Migacz et al, 2021 ). Fourth, Cys-C is also known as neutrophil growth factor and is involved in the migration, phagocytosis, and inflammation of neutrophils.…”
Section: Discussionmentioning
confidence: 99%